Study on Potential Waste Insulating Material Properties in Water for Thermal Storage Application - Tanti Zanariah, Shamshir Ali; R. A., Bakar; Gan, Leong Ming; Billy, Anak Sup; Mohd Farid, Zainudin (Trans Tech Publications, Switzerland, 2014)
Energy is a continuous driving power for the social and technological development. Developing thermal energy storage(TES) is a competent way to provide continuous power generation. The key issue in designing the TES system is its thermal capacity of storage materials. This study is focusing on the potential waste material as an insulator for thermal energy storage applications. The insulator usage is to reduce the heat transfer between two medium and the capability is measured by its heat flow resistance. The bigger the value, the more blocking capacity or insulating it provides. It is needed to find optimal material to energy conversion at the same time reduce the waste generation. Therefore, a small-scale experimental testing of natural cooling process of an insulated tank within a confined room without any forced cooling system, e.g. fan. The testing is repeated by changing the insulator using the potential waste material from natural and industrial waste. The analysis is performed on the relationship between heat loss and the reserved period by the insulator. The results represent the percentage of period of the insulated tank withstand the heat compared to non-insulated tank, e.g. cotton reserved the period of 19% more than non-insulated tank to withstand the heat transfer of water to the surrounding. The paper finally justifies that cotton is the most potential waste material as an insulator in water.